Salt light absorption material and photo-thermal energy storage integration
The metal oxide and salt composite materials with nanoporous structures achieve full-wavelength absorption and efficient photo-thermal conversion, solving the problems of thermal energy loss and high equipment costs in photo-thermal conversion materials, and improving solar energy utilization efficiency and heat storage density.
Patent Information
- Application Number
- CN202411167384.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-08-23
- Publication Date
- 2024-12-27
AI Technical Summary
The existing photothermal conversion materials have problems of thermal energy loss and high equipment cost in the process of absorbing solar energy and storage of heat, and it is difficult for heat storage materials to achieve full-wavelength solar energy absorption and high-efficiency photothermal conversion.
The metal oxide and salt composite material with nanoporous structure is used as the integrated photothermal storage material, absorbing solar energy through full wavelength and directly performing photothermal conversion and heat storage, reducing the number of equipment and thermal energy transmission process.
It realizes efficient photothermal conversion and heat storage, reduces equipment costs and thermal energy losses, and improves solar energy utilization efficiency and heat storage density.
Smart Images

Figure CN119193114A_ABST
Abstract
Description
Technical Field
[0001] It belongs to the field of new energy, solar energy and energy storage technology, and specifically involves light absorption materials and integrated photothermal heat storage materials. Technical Background
[0002] Solar energy is a huge green energy source, and a huge amount of solar radiation is projected onto the earth every day. Photothermal utilization is the main way to utilize solar energy. Photothermal power generation has been applied on a large scale, and molten salt is used to store high-temperature solar energy. By the end of 2021, the installed capacity of global photothermal power stations will be about 6.6GW. Photothermal conversion materials are the key to solar thermal utilization, and the performance of the materials directly affects the utilization efficiency of solar energy; excellent photothermal materials should have high absorbance, be able to absorb sunlight at all wavelengths, have high photothermal conversion efficiency, and have low material cost.
[0003] In addition, volatility and seasonality affect the utilization of solar energy, and this problem can be solved by energy storage technology. Energy storage technology can promote energy production and consumption, flexible trading, coordinated development, open sharing, and promote the development and utilization of energy revolution and new energy. It is the core support for the development of new energy and renewable energy. The innovative breakthroughs in energy storage technology will become an important leading technology to drive revolutionary and subversive adjustments in the global energy structure. Compared with technologies such as electrochemical energy storage and electrical energy storage, thermal storage technology has significant advantages in installed capacity, energy storage density, energy storage cost and service life. Compared with compressed air energy storage and pumped storage, thermal storage technology has high energy storage density, small footprint, low cost, small impact on the environment, and is not restricted by geographical and environmental conditions. Thermal energy storage technology is also a large-capacity and large-scale energy storage method with high energy density and high conversion efficiency. It can play an important role in building a new power system with new energy as the main body, ensuring the safe and stable operation of the power system, and building a clean, low-carbon, safe and efficient energy system.
[0004] Chemical heat storage technology uses reversible thermochemical reactions to complete heat storage and heat release; for example, lime meets water to form slaked lime and releases a large amount of heat energy (1400kJ / kg), and slaked lime is heated and dehydrated to form lime to complete heat storage. The water absorption and dehydration process of the hydrate completes heat release and heat storage. The energy storage density of chemical heat storage technology is several times that of molten salt heat storage, and the high-temperature solar energy in summer can be stored for use in winter, and there is almost no heat energy loss in the heat storage process. Water and molten salt heat storage is sensible heat storage, with heat energy loss, and is suitable for heat storage in a limited time. The present invention discloses a new and efficient photothermal material that can not only absorb sunlight in full wave, but also has a high photothermal conversion efficiency, and the material has a salt with a nanoporous structure. The new light-absorbing material is used to modify the heat storage material to form a new type of photothermal storage integrated material. The photothermal storage integration can reduce the number of equipment, reduce the cost of photothermal storage equipment, shorten the photothermal storage process, and improve the efficiency and economic benefits of the photothermal storage system. Summary of the invention
[0005] Solar energy is inexhaustible. Solar energy can be divided into ultraviolet light, visible light and near-infrared light, and the amounts of these three parts are about 5%, 45% and 50% respectively; visible light and near-infrared light account for about 95% of solar energy. Efficient use of solar energy requires light-absorbing materials that can absorb solar energy in the full spectrum, however, such materials are rare; the present invention provides materials that can absorb solar energy in the full spectrum. In addition, traditional solar energy technology uses pipes and heat transfer fluids to transmit heat energy, and this process not only causes heat energy loss, but also increases equipment and maintenance costs. If the heat storage material can directly convert light energy into heat energy and complete heat storage, the heat exchange and heat energy transmission process and related equipment can be omitted, which has the advantage of practical application. To solve the scientific problem of direct absorption of solar energy by heat storage materials, photothermal materials can be used to enhance the absorbance and photothermal conversion efficiency of heat storage materials, so that they can complete the absorption of solar energy, photothermal conversion and heat storage processes in one step.
[0006] Thermal storage technology includes three methods: sensible heat storage, phase change heat storage and chemical heat storage. The materials for sensible heat storage include water and molten salt, and the materials for chemical heat storage are substances that can undergo reversible thermochemical reactions, such as lime, limestone, magnesium hydroxide, hydrates, and multivalent oxides that can undergo redox reactions, such as copper oxide, iron oxide, nickel oxide, cobalt oxide, and manganese oxide; synthetic ammonia reactions, methane, etc.
[0007]
[0008] For the heat storage of hydroxides and hydrates, the dehydration reaction stores heat and the hydration reaction releases heat. Lithium hydroxide, magnesium hydroxide and calcium hydroxide are abundant raw materials and have the most application prospects. The heat storage density is greater than 1300 kJ / kg, which is several times that of molten salt (Formulas 1 and 2). Similar to hydroxides, hydrates can also undergo water absorption and release heat and dehydration and heat storage reactions, and can be used for heat storage. For example, MgSO 4 ·XH 2 O,Na 2 SO 4 10H 2 O,AlK(SO 4 ) 2 ·XH 2 O,CaCl 2 ·XH 2 O,SrBr 2 ·XH 2 O,LiOH·H 2 O,Sr(OH) 2 ·XH 2 O etc.
[0009] The present invention relates to light absorbing materials, which are used to enhance the absorbance and photothermal conversion rate of heat storage materials, and to achieve light absorption and heat storage technology at the same time. For example, the light absorbing material of the present invention is used in combination with various heat storage materials to obtain a heat storage material that integrates light, heat and heat storage, which is used to store and release heat. The heat storage materials of the present invention include sensible heat storage materials, phase change heat storage materials and chemical heat storage materials. For example, sensible heat storage materials include molten salt, water paraffin, heat transfer oil and other organic and inorganic substances. Phase change heat storage materials include various inorganic and organic phase change materials. Chemical heat storage materials include various substances with reversible thermochemical reactions. The hydroxide heat storage material is selected from magnesium hydroxide, aluminum hydroxide, lithium hydroxide, strontium hydroxide, boric acid and calcium hydroxide; the hydrate heat storage material is selected from sodium sulfate hydrate, calcium sulfate hydrate, copper sulfate hydrate, magnesium sulfate hydrate, aluminum sulfate hydrate, potassium aluminum sulfate hydrate, sodium thiosulfate hydrate, sodium carbonate hydrate, calcium bromide hydrate, magnesium bromide hydrate, lithium chloride hydrate, lithium nitrate hydrate, zinc nitrate hydrate, iron nitrate hydrate, calcium nitrate hydrate, lanthanum nitrate hydrate, magnesium nitrate hydrate, strontium bromide hydrate, strontium chloride hydrate, calcium chloride hydrate, magnesium chloride hydrate, lanthanum chloride hydrate, lithium hydroxide hydrate, strontium hydroxide hydrate, sodium hydroxide hydrate, potassium hydroxide hydrate, magnesium chloride hydrate, iron chloride hydrate, aluminum chloride hydrate, sodium phosphate hydrate and sodium hydrogen phosphate hydrate.
[0010] 1. The light absorbing material of the present invention is characterized by being able to absorb solar energy at all wavelengths, having high light absorption efficiency and high photothermal efficiency. The design principle of the light absorbing material of the present invention is to utilize crystal field theory, utilize the differences in energy bands of different crystal planes and interfaces of different substances to construct homogeneous and heterogeneous structures, and the photothermal principle of nanostructures to adjust the band gap and carrier concentration to achieve full wavelength absorption. The light absorbing material of the present invention can also be used for photocatalytic chemical reactions, photothermal reactions, decomposition of water and pollutants, photothermal treatment of diseases, photothermal energy storage, photothermal power generation, photothermal buildings, photothermal sensors, etc. The light absorbing material of the present invention is composed of metal oxides and salts; the metal oxides are selected from cobalt oxides, iron oxides, strontium oxides, chromium oxides, nickel oxides, copper oxides, vanadium oxides, manganese oxides, strontium oxides, titanium oxides, lanthanum oxides, cerium oxides, aluminum oxides, zinc oxides, calcium oxides, magnesium oxides, boron oxides, silver oxides, lead oxides, selenium oxides, tin oxides, tellurium oxides, indium oxides, gallium oxides, zirconium oxides, hafnium oxides, mercury oxides, tungsten oxides and molybdenum oxides; the salts are selected from metal silicates, metal sulfates, metal phosphates, metal carbonates, metal borates and metal phosphosilicates; the metal of the metal salts is selected from iron, cobalt, nickel, copper, zinc, aluminum, calcium, magnesium, vanadium, chromium, manganese, lanthanum, titanium, cerium, strontium, silver, tin, selenium, gallium, lead, zirconium, hafnium, indium, mercury, lithium, sodium, potassium, tungsten and molybdenum.
[0011] The light absorbing material can be a composite of a metal oxide and a salt, a composite of two metal oxides and a salt, a composite of two metal oxides and two salts, a composite of a metal oxide and two salts, or any combination of multiple metal oxides and multiple salts. The mass content of the salt is 0.1%-85%, preferably 5%-60%.
[0012] Composite light-absorbing material of metal oxides and silicates, cobalt oxide-cobalt silicate, Co 2 SiO 4 –x mol%Co 3 O 4 , x = 10, 20, 30, 50, 67 and 80. The absorbance curves of various materials are as follows: Figure 1 , absorbance Figure 2, It can be seen that the material with x=20 has the highest absorbance; Co 2 SiO 4 –20 mol% Co 3 O 4 The photothermal temperature can reach 723℃( Figure 3) .Co 2 SiO 4 –20 mol% Co 3 O 4 and Mg(OH) 2 Composition of complex, Mg(OH) 2 –18wt%(Co 2 SiO 4 –20 mol% Co 3 O 4 ) The photothermal temperature is 705℃, and the photothermal temperature under different light intensities is shown in Figure 4; The photothermal temperature can reach the highest level after about 30 seconds of illumination. Photothermal dehydration stores heat and rehydration releases heat. After 40 minutes of photothermal dehydration, the dehydration conversion rate reaches 96%.
[0013] Metal oxide and phosphate composite light-absorbing material, cobalt oxide-cobalt phosphate, Co 3 O 4 –x-mol%Co 3 (PO 4 ) 2 The absorbance curves of x=5, 20 and 37 are as follows: Figure 5; Figure 5 and Figure 6 Table Ming Co 3 O 4 –20-mol%Co 3 (PO 4 ) 2The absorbance of the material is the highest, and the absorbance of other materials is relatively low. 3 O 4 –20-mol%Co 3 (PO 4 ) 2 The photothermal temperature can reach 682℃. 3 O 4 –20-mol%Co 3 (PO 4 ) 2 and Ca(OH) 2 Composition of complex, Ca(OH) 2 –2.5mol%(Co 2 SiO 4 –20 mol% Co 3 (PO 4 ) 2 )The photothermal temperature is 675℃; the photodehydration conversion rate can reach 97% ( Figure 7) , light dehydration heat storage, rehydration heat release, after 30 cycles of heat storage and release, the dehydration conversion rate is 94% ( Figure 8) .Co 3 O 4 –20-mol%Co 3 (PO 4 ) 2 and Ca(OH) 2 –2.5mol%(Co 2 SiO 4 –20 mol% Co 3 (PO 4 ) 2 ) reveals the nanostructure of the material, see Figure 9 and Figure 10. Figure 11 Co 2 SiO 4 –20 mol% Co 3 O 4 Scanning electron microscope image.
[0014] For multivalent metals, it can be oxides of various valent metals and mixtures thereof; these oxides are mixed with silicates to form light-absorbing materials. Silicates have a layered structure, which is conducive to the formation of nano two-dimensional structural materials and to enhance the absorption of light; this type of light-absorbing material can be composed of one or more metal oxides and a plurality of silicates, and the silicates can also be a variety of silicates, one or more can be used; the content of silicates is 0.1%-85%. Other types of salts, such as metal sulfates, metal phosphates, metal carbonates, metal borates and metal phosphosilicates, etc. can be used, and the compound with metal oxides is similar to the silicates mentioned above.
[0015] The above-mentioned photothermal material is mixed with the above-mentioned heat storage material to obtain a composite material. These composite materials are also integrated photothermal storage materials, which can absorb solar energy. After absorbing solar energy, the temperature rises and a dehydration reaction occurs to complete heat storage. The heat storage material is selected from magnesium hydroxide, aluminum hydroxide, lithium hydroxide, strontium hydroxide, boric acid and calcium hydroxide, sodium sulfate hydrate, calcium sulfate hydrate, copper sulfate hydrate, magnesium sulfate hydrate, aluminum sulfate hydrate, potassium aluminum sulfate hydrate, iron sulfate hydrate, sodium carbonate hydrate, calcium chloride hydrate, strontium bromide hydrate, iron nitrate hydrate, manganese nitrate hydrate, calcium nitrate hydrate, magnesium nitrate hydrate, lithium hydroxide hydrate, strontium hydroxide hydrate, magnesium chloride hydrate, iron chloride hydrate, aluminum chloride hydrate, sodium phosphate hydrate and sodium hydrogen phosphate hydrate. The photothermal material can be a mixture of one, two or more of the above-mentioned photothermal materials, and the heat storage material can also be a mixture of one, two or more of the above-mentioned heat storage materials; the photothermal material promotes the heat storage material to absorb and store solar energy. In integrated solar-thermal-storage materials, the mass of light-absorbing materials accounts for 2-60%. Specific embodiments
[0016] Embodiment 1,
[0017] Preparation of silicates and photothermal temperature
[0018] MnCl 2 ·4H 2 O (9.9 g) and a certain proportion of Cu (NO 3 ) 2 Dissolve in 50ml deionized water and dissolve completely; Na 2 SiO 3 (6.1 g) was dissolved in deionized water (50 ml); the solution was mixed and stirred for 20 min, dehydrated and dried at 120 °C, kept at 350 °C for 3 h, and kept at 650 °C for 5 h. It was cooled to room temperature, washed with deionized water (5 mL x 3), and dried at 120 °C overnight to obtain CuO-x mol% MnO x -ymol%Mn 2 SiO 4Light-absorbing material. Photothermal temperature 649℃.
[0019] Embodiment 2,
[0020] Preparation and photothermal temperature of magnesium hydroxide + silicate
[0021] a. 4 mL of water and ethanol (volume ratio 3:1) Mn(NO 3 ) 2 and Fe(NO 3 ) 3 9H 2 O (0.63 g) was dissolved by stirring.
[0022] b.Na 2 SiO 3 (0.285 g) was added with water (3 mL) and stirred to dissolve.
[0023] c. Deionized water (10 mL), slowly add amino acid (0.55 g) in batches, stir until completely dissolved; then add Mg(OH) 2 (1.5g), stir slowly for 10min. Add the above solution a and stir for 10min. Then slowly add solution b, and let it stand for 3h after adding. Heat to 90℃ to evaporate to form a colloid; dry in a drying oven at 120℃ to obtain a solid. Heat to 190℃ and keep warm for 3h; then heat to 500℃ and keep warm for 5h. Cool to room temperature, wash with deionized water (5mL x 3), add 5ml deionized water, hydrate at 110℃ for 1h, and dry at 120℃ for 4h to obtain a porous solid FeOx-x mol% MnO x -y mol%Mn 2 SiO 4 -Mg(OH) 2 The photothermal temperature under xenon lamp irradiation was 646°C and the dehydration conversion rate was 93%.
[0024] Embodiment 3,
[0025] Co(NO 3 ) 2 (0.58 g) and a certain amount of Na 2 SiO 3 Deionized water (3 mL) was added, stirred for 10 min, and the temperature was raised to 120 °C and dried to obtain a solid. The temperature was then raised to 360 °C and kept for 3 h; the temperature was then raised to 600 °C and kept for 5 h. After cooling to room temperature, the mixture was washed with deionized water (5 mL x 3) and dried at 120 °C to obtain a solid Co 2 SiO 4 –x mol%Co 3 O 4 , x = 10, 20, 30, 50, 67 and 80. The absorbance curves of various materials are as follows: Figure 1 , absorbance Figure 2. The material with x=20 has the highest absorbance; Co 2 SiO 4 –20 mol% Co 3 O 4 The photothermal temperature can reach 723℃( Figure 3) .SEM Figure 11 Table Nanostructure. 2 SiO 4 –20 mol% Co 3 O 4 and Mg(OH) 2 Composition of complex, Mg(OH) 2 –18wt%(Co 2 SiO 4 –20 mol% Co 3 O 4 ) The photothermal temperature is 705℃, and the photothermal temperature under different light intensities is shown in Figure 4; The photothermal temperature can reach the highest level after about 30 seconds of illumination. Photothermal dehydration stores heat and rehydration releases heat. After 40 minutes of photothermal dehydration, the dehydration conversion rate reaches 96%.
[0026] Embodiment 4,
[0027] Sr(NO 3 ) 2 (0.423 g) and Na 2 SO 4 (0.285 g) was added with deionized water (10 mL) and stirred for 20 min; Ni(NO 3 ) 2 (1.6g) and Co(NO 3 ) 2 6H 2 O (1.164 g), stirred to dissolve, added ethanol (10 mL); then added Ca(OH) 2 (1.3g), stirred and added with ammonia water until alkaline. After washing with deionized water (5mL x 3), the temperature was raised to 140℃, kept warm for 1h, and then placed in a muffle furnace and raised to 350℃, kept warm for 6h, and then raised to 850℃ for calcination for 3h. After cooling to room temperature, 2mL of water was added, and after 0.5h, NiO-CoOx-SrSO was obtained after drying at 100℃ for 4h. 4 -y mol%Ca(OH) 2 Photothermal porous material, the tested photothermal temperature is 716℃. The dehydration conversion rate is 93% after 50 minutes of illumination.
[0028] Embodiment 5,
[0029] Cu(NO 3 ) 2 and Na3 PO 4 (0.285 g) was added with deionized water (10 mL) and stirred for 10 min, then amino acid (1.12 g) and ethanol (10 mL) were added, and Mn(NO 3 ) 2 and Co(NO 3 ) 2 (0.58 g), stirred for 10 min; then added Ca(OH) 2 (1.3g), add ammonia water to make it alkaline, continue stirring at room temperature for 0.3h to completely precipitate the metal ions; place it at room temperature for aging for 2h. After washing with deionized water (5mL x 3), the obtained product was dried at 140℃ for 3h and 350℃ for 3h; then heated to 850℃ and calcined for 4h. Cool to room temperature, add 2mL of water, and after 0.5h, dry at 100℃ for 4h to obtain MnOx-CoOy-Cu 3 (PO 4 ) 2 -Ca(OH) 2 The photothermal porous material has a tested photothermal temperature of 683°C and a dehydration conversion rate of 96% after 50 minutes of illumination.
[0030] Embodiment 6,
[0031] Equivalent CaCl 2 and Na 2 SiO 3 Mix and stir for 10 min to obtain CaSiO 3 , deionized water (10 mL), tartaric acid (1.12 g) and ethanol (10 mL) were added, and Ce(NO 3 ) 3 6H 2 O (0.87 g) and Co (NO 3 ) 2 (0.58 g), stirred for 10 min; then added Ca(OH) 2 (1.3 g), stirred and added with ammonia water to completely precipitate the metal ions; aged at room temperature for 2 h. Filtered, washed with deionized water (5 mL x 3), the resulting product was dried at 140 ° C for 3 h, heated to 400 ° C for pre-calcination for 2 h, and then heated to 850 ° C for calcination for 3 h. Cooled to room temperature, added with 2 mL of water, and after 0.5 h, dried at 100 ° C for 4 h to obtain CoOx-CeOy-CaSiO 3 -Ca(OH) 2 Porous photothermal material, the tested photothermal temperature is 672℃. The dehydration conversion rate is 95% after 50 minutes of illumination.
[0032] Embodiment 7,
[0033] Na 3PO 4 (0.385 g) and FeCl 3 (0.33 g) was dissolved in deionized water (10 mL), stirred for 10 min, and amino acid (1.12 g) and ethanol (10 mL) were added. Mn(NO 3 ) 2 (0.58g) and Ni(NO 3 ) 2 (0.58 g) was placed in an oil bath at 85 °C and stirred continuously to obtain a slurry. The obtained product was dried at 160 °C for 3 h, heated to 400 °C for pre-calcination for 2 h, and then heated to 650 °C for calcination for 3 h. After cooling to room temperature, washing with deionized water (5 mL x 3), and drying at 100 °C for 4 h, MnOx-NiO-FePO 4 Porous light-absorbing material, the tested photothermal temperature is 679℃.
[0034] Embodiment 8,
[0035] Equal amount of Na 2 SiO 3 and Cu(NO 3 ) 2 Mixed to obtain CuSiO 3 , deionized water (10 mL), amino acid (1.12 g) and ethanol (10 mL), Zn(NO 3 ) 2 (1.18 g) and Co(NO 3 ) 2 (0.58 g), stirred for 10 min; then added Ca(OH) 2 (1.3 g), stirred and added with ammonia water (10 mL) to completely precipitate the metal ions; filtered, washed with deionized water (5 mL x 3), and dried at 160 ° C for 3 h, and then at 300 ° C for 3 h; heated to 400 ° C for pre-calcination for 2 h, and then heated to 850 ° C for calcination for 3 h. Cooled to room temperature, added with 2 mL of water, and dried at 100 ° C for 4 h to obtain ZnCoxOy-CuSiO 3 -Ca(OH) 2 Porous photothermal material, the photothermal temperature is 674℃. The dehydration conversion rate is 97% after 60 minutes of illumination.
[0036] Embodiment 9,
[0037] Cu(NO 3 ) 2 (0.68 g) and Na 2 SiO 3 (0.385 g) was dissolved in water (20 mL) and ethanol (10 mL), stirred for 20 min, and Ni(NO 3 )2 (0.68 g), stirred for 20 min. The mixture was stirred at 85 ° C to obtain a slurry, and the obtained product was dried at 160 ° C for 3 h, heated to 400 ° C for pre-calcination for 2 h, and then heated to 650 ° C for calcination for 3 h. The photothermal storage material CuO-NiO-Cu 2 SiO 4 , photothermal temperature 684℃.
[0038] Embodiment 10,
[0039] Cobalt oxide - cobalt phosphate, Co 3 O 4 –x-mol%Co 3 (PO 4 ) 2 The absorbance curves of x=5, 20 and 37 are as follows: Figure 5; Figure 5 and Figure 6 Table Ming Co 3 O 4 –20-mol%Co 3 (PO 4 ) 2 The absorbance of the material is the highest, and the absorbance of other materials is relatively low. 3 O 4 –20-mol%Co 3 (PO 4 ) 2 The photothermal temperature can reach 682℃. 3 O 4 –20-mol%Co 3 (PO 4 ) 2 and Ca(OH) 2 Composition of complex, Ca(OH) 2 –2.5mol%(Co 2 SiO 4 –20 mol% Co 3 (PO 4 ) 2 )The photothermal temperature is 675℃; the photodehydration conversion rate can reach 97% ( Figure 7) , light dehydration heat storage, rehydration heat release, after 30 cycles of heat storage and release, the dehydration conversion rate is 94% ( Figure 8) .Co 3 O 4 –20-mol%Co 3 (PO 4 ) 2 and Ca(OH) 2 –2.5mol%(Co 2 SiO 4 –20 mol% Co3 (PO 4 ) 2 ) reveals the nanostructure of the material, see Figure 9 and Figure 10.
[0040] Embodiment 11,
[0041] Calcium chloride hydrate, CuO—10mol%Cu 3 (BO 3 ) 2 Light temperature 337℃, CaCl 2 5H 2 O—16wt%(CuO—10mol%Cu 3 (BO 3 ) 2 ) Light temperature is 332℃ and the dehydration rate is 100%.
[0042] Example 12,
[0043] Lithium hydroxide hydrate, CoO x —20 mol% Co 3 (BO 3 ) 2 The photothermal temperature is 377℃, LiOH 2H 2 O—15wt%(CoO x —20 mol% Co 3 (BO 3 ) 2 )'s photothermal temperature is 357°C, and the photodehydration rate is 98%.
[0044] Embodiment 13,
[0045] Na 2 SO 4 10H 2 O—15wt%(CoO x —20 mol% Co 3 (BO 3 ) 2 )'s photothermal temperature is 365°C, and the photothermal dehydration rate is 98%.
[0046] Embodiment 14,
[0047] MgSO 4 6H 2 O—15wt%(CoO x —20 mol% Co 3 (BO 3 ) 2 )'s photothermal temperature is 372°C, and the photodehydration rate is 97%. BRIEF DESCRIPTION OF THE DRAWINGS
[0048] Figure 1 .Co 2 SiO 4 —x mol%CoO x Absorbance curve of photothermal material
[0049] Figure 2. Co 2 SiO 4 —x mol%CoO x The relationship between absorbance and content (X).
[0050] Figure 3. Co 2 SiO 4 —x mol%CoO x Relationship between photothermal temperature and content of photothermal materials
[0051] Figure 4. Mg(OH) 2 –x wt%(Co 2 SiO 4 –20 mol% Co 3 O 4 )The relationship between photothermal temperature and illumination time.
[0052] Figure 5. Co 3 O 4 –x-mol%Co 3 (PO 4 ) 2 Absorbance curve of photothermal material
[0053] Figure 6. Co 3 O 4 –x-mol%Co 3 (PO 4 ) 2 The relationship between absorbance and content (X).
[0054] Figure 7. Ca(OH) 2 –2.5mol%(Co 3 O 4 –20 mol% Co 3 (PO 4 ) 2 )The relationship between photothermal dehydration conversion rate and illumination time.
[0055] Figure 8. Ca(OH) 2 –2.5mol%(Co 3 O 4–20 mol% Co 3 (PO 4 ) 2 )and Ca(OH) 2 The relationship between dehydration conversion rate and the number of heat storage and release cycles.
[0056] Figure 9. SEM-Co 3 O 4 -20 mol% Co 3 (PO 4 ) 2 .
[0057] Figure 10. SEM imageCa(OH) 2 –2.5mol%(Co 3 O 4 -20 mol% Co 3 (PO 4 ) 2 )
[0058] Figure 11. SEM imageCo 2 SiO 4 –20 mol% Co 3 O 4。
Claims
1. A light absorbing material, characterized in that: The light absorbing material is composed of metal oxides and metal salts; the metal salts are selected from metal silicates, metal sulfates, metal phosphates, metal carbonates and metal borates, and the metal of the salts is selected from iron, cobalt, nickel, copper, zinc, aluminum, calcium, magnesium, vanadium, chromium, manganese, lanthanum, titanium, cerium, strontium, silver, tin, selenium, gallium, lead, zirconium, hafnium, indium, mercury, lithium, sodium, potassium, tungsten and molybdenum; the metal oxides are selected from oxides of iron, cobalt, nickel, copper, zinc, aluminum, calcium, magnesium, vanadium, chromium, manganese, lanthanum, titanium, cerium, strontium, silver, tin, selenium, gallium, lead, zirconium, hafnium, indium, mercury, lithium, sodium, potassium, tungsten and molybdenum.
2. The light absorbing material according to claim 1, characterized in that: The light absorbing material may contain one metal salt, two metal salts, three metal salts or multiple metal salts; the metal oxide contained in the light absorbing material may contain one metal oxide, two metal oxides or multiple metal oxides. The mass content of the salt is 0.1%-85%, preferably 5%-60%.
3. Photothermal energy storage integrated material, characterized by: The integrated photothermal storage material consists of a heat storage material and a light absorbing material; the light absorbing material is selected from the light absorbing material described in claim 1; the mass of the light absorbing material accounts for 2%-60% of the total.
4. The integrated light-heat-storage material according to claim 3, characterized in that: The heat storage material is selected from latent heat storage materials, sensible heat storage materials and chemical heat storage materials, including paraffin, silicone oil, molten salt, magnesium hydroxide, aluminum hydroxide, lithium hydroxide, strontium hydroxide, boric acid, calcium hydroxide, sodium hydroxide, calcium carbonate, sodium sulfate hydrate, calcium sulfate hydrate, copper sulfate hydrate, magnesium sulfate hydrate, aluminum sulfate hydrate, potassium aluminum sulfate hydrate, sodium thiosulfate hydrate, sodium carbonate hydrate, lithium nitrate hydrate, zinc nitrate hydrate, iron nitrate hydrate, calcium nitrate hydrate, lanthanum nitrate hydrate, magnesium nitrate hydrate, calcium bromide hydrate, magnesium bromide hydrate, strontium bromide hydrate, lithium chloride hydrate, strontium chloride hydrate, calcium chloride hydrate, magnesium chloride hydrate, lanthanum chloride hydrate, iron chloride hydrate, aluminum chloride hydrate, lithium hydroxide hydrate, strontium hydroxide hydrate, sodium hydroxide hydrate, potassium hydroxide hydrate, sodium phosphate hydrate, sodium hydrogen phosphate hydrate and mixed heat storage materials.
